PENGETAHUAN MEMPENGARUHI PEMILIHAN KB SUNTIK PADA AKSEPTOR YANG MEMERIKSAKAN DIRI BIDAN PRAKTEK MANDIRI DI TANGERANG - Ernamesra Ernamesra Ernamesra; Fauziah Fauziah Fauziah (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
The National Family Planning movement has an aim to embody the small happy and welfare family that become a base of materialized to a welfare society through the birth controlling and the growth of Indonesian inhabitant. One of them is by birth controlling through contraception. Injection contraception is one of the way to prevent the pregnancy by hormonal injection contraception method shows the increasing for the last few years. In Indonesia, the usage Family Planning (KB) injection has the most, which is 47,94%, the second is the usage of pills, the third is IUD (Intra uterine Device) implants, condoms, and the last method of male and female operations. The reason is because the injection method more effective, practical, the price of cheap and also save. The aim is to know the distribution of injection acceptors and dominant factors that related with injection method preference. Research’s design using Cross Sectional sample of 142 respondents. The conclusion is 61.97% for acceptors of per 3 months injection and 38.3% for acceptors of per 1 month injection, there are also connection to the ages, education, and knowledge, the most dominant variable is knowledge of acceptors P Value 0,000 and OR 150.430, which has meaning the good knowledge has effect to the choosing of injection method 150.430 times bigger than them that have less knowledge of it. The suggestion of increasing the Knowledge of Human Resource in health especially to all midwives by routine trainings so they can give the excellent service to all Family Planning acceptors.